2017
DOI: 10.1074/jbc.m117.780007
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the PH and START domains of ceramide transfer protein competes with phosphatidylinositol 4-phosphate binding by the PH domain

Abstract: synthesis of the sphingolipid sphingomyelin requires non-vesicular transport of ceramide from the endoplasmic reticulum to the Golgi by the multidomain protein ceramide transfer protein (CERT). CERT's N-terminal pleckstrin homology (PH) domain targets it to the Golgi by binding to phosphatidylinositol 4-phosphate (PtdIns(4)P) in the Golgi membrane, whereas its C-terminal StAR-related lipid transfer domain (START) carries out ceramide transfer. Hyperphosphorylation of a serine-rich motif immediately after the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 49 publications
0
55
0
Order By: Relevance
“…This model was recently supported by a structural study by Prashek et al (20), who showed that isolated PH and START domains of CERT interacted with each other and that specific regions on the surface of the PH domain, which are involved in the interaction between the two domains, are partially overlapped with the PI4P-binding site. In addition, Prashek et al (20) demonstrated that amino acid substitutions in the PH-START-interacting surface abrogated the repressive effects of the CERT 10E mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model was recently supported by a structural study by Prashek et al (20), who showed that isolated PH and START domains of CERT interacted with each other and that specific regions on the surface of the PH domain, which are involved in the interaction between the two domains, are partially overlapped with the PI4P-binding site. In addition, Prashek et al (20) demonstrated that amino acid substitutions in the PH-START-interacting surface abrogated the repressive effects of the CERT 10E mutation.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the interaction between the PH domain and phosphorylated SRM can be an "intermediate" form toward a more drastic conformational rearrangement of CERT and will lead the PH-START interdomain interaction for mutually and functionally silencing conformations. The START domain is required for the repression of the PI4P-binding activity of the CERT PH domain under these conditions (9,20). The inactive conformer is mainly distributed in the cytosol as an inactive pool of CERT, whereas inactive CERT is dephosphorylated in response to specific stimuli (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Xray crystallography with the purified CERT PH and START domains revealed that a basic groove in the PH domain snugly binds to the negatively charged loop of the START domain [43]. Mutations disrupting the PH/START interaction increase both PtdIns(4)Pbinding activity and ceramide-transfer activity of CERT 10E, thereby supporting the inter-domain steric hindrance model [43]. The CERT PH domain also electrostatically interacts with the phosphor-mimetic SRM (SRM 10E; Fig.…”
Section: Serine-repeat Motifmentioning
confidence: 95%
“…LTP targeting can be regulated by post-translational modification. CERT targeting is affected by two different phosphorylations, one of which activates the FFAT, while the other causes autoinhibitory binding of the PH and StARkin domains [70][71][72] . LTPs and their localisation can also be regulated by Ca 2+ signalling.…”
Section: Dual Membrane Targeting Domainsmentioning
confidence: 99%